Impact of COVID-19 on mutual fund performance in Saudi Arabia - Haidar Alqadhib; Nada Kulendran; Lalith Seelanatha (Cogent Economics & Finance, 2022)
This study aims to measure the performance of actively-managed Saudi Arabia mutual funds during the COVID-19 outbreak and examines the potential impact of COVID-19 growth on the measured performance. The authors apply the Fama and French five-factor model to measure the risk-adjusted performance of a selected sample of 79 mutual funds. Mutual funds in Saudi Arabia outperformed the market with a significant positive alpha of 0.15%. The panel data regression technique identified the impact of growth in new confirmed cases and fatalities with fund-specific variables on mutual fund performance. The findings suggest that new confirmed cases had a significant and negative impact on mutual fund unadjusted returns and risk-adjusted returns. The significant positive impact of growth in COVID-19 fatalities on fund performance may have been interpreted as positive news by the market participants as the actual mortality rate was lower than previous forecast. Moreover, the study found that even individually, most mutual fund managers were not able to minimise the impact of the COVID-19 outbreak on mutual fund returns compared to the market portfolio. This study examines the potential impact of growth in COVID-19 cases as a new factor affecting mutual fund performance which helps investors to understand the behaviour of mutual fund performance during the COVID-19 crisis. It also provides evidence on how mutual fund performance reacted to the COVID-19 outbreak when compared to the overall market performance reaction. Moreover, this is the first study that applied the Fama and French five-factor model to estimate the mutual funds' risk-adjusted performance.
Keywords: 330; COVID-19; mutual fund performance; Saudi Arabia; stock market; Fama and French five-factor model